The family creative workshop : home-finished furniyure, hooked rugs, ice-cream sorbets and ice, ikebana, inkle weaving, jewellery, kaleidoscopes, kayaks, kilns, kites, knitting to fit, lace - Bragdon, Allen Davenport (Plenary Publications International, 1975)
128 p. : il.; 27 cm.